Synthesis and Characterization of Complexes of Mn (II), Co(II) and Zn(II) with Schiff Base - Parihari, R.K.; Patel, R.N. (Asian Journal of Chemistry, 2012)
The organic Schiff base ligand, salicylidene anthranilic acid have been synthesized from salicylaldehyde and anthranilic acid. Ten complexes of Mn(II), Co(II) and Zn(II) have been prepared by taking metal salt, the lignad salicylidine anthranilic acid and some neutral ligands (pyridine, isoquinoline, quinoline, γ-picoline). Complexes and ligand are characterized on the basis of their elemental analysis, molecular weight measurements, conductance measurements, magnetic susceptibility measurements, UV and IR spectral data.